Bioprospecting of sponge and its symbionts: New tool for mosquitocidal & insecticidal metabolites. (May 2019) - Mathivanan, A.; Ravikumar, S.; Selvakumar, G.
Abstract: Vector borne disease is a global threat and chemical, biopesticides have been employed for their control. Application of pyrethroid in Long Lasting Insecticide treated Nets (LLIN) for the prevention of mosquito bite and alarming resistance of this compound lead to global issue. Wide usage of chemical pesticides and its resistance in mosquito urged the research community to find better alternatives for mosquito control. Sponges (phylum Porifera) are primitive aquatic metazoans since 600 million years and comprised of 8600 species till date and existing in various habitats. Sponges symbiotic microbes are involved in nutrition, nitrogen fixation, nitrification, defense, skeleton stabilization of the invertebrate host. Many insecticidal molecules such as manzamine, Jaspamide, alkaloids and terpenoids have been identified from marine sponges and Mosquitocidal activity from several sponge extracts from Dendrila nigra, Haliclona cribricutis etc. were reported. In this connection, sponges and sponge associated microbes were really unexplored much for vector control. Ideally, novel leads from sponges and sponge associated microbes could be a prospective source for new vector control tool. Graphical abstract: Image 1 Highlights: Marine sponge & sponge symbionts as novel initiative for vector control tool. Promising alternative source to obtain diversified novel leads. Generate chemical library with the help of bioinformatics tools to ascertain mosquitocidal activity. Prospective translational research to identify mosquitocidal molecule with good efficacy.